Dialektika Fikih Musyarakah Mutanaqisah: Analisis Kritis Penerapannya dalam Pembiayaan Perumahan Syariah di Indonesia - Abdul Fattah; Sofyan al-Hakim; Fauzan Januri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This paper presents a comprehensive analysis of the jurisprudential dialectic surrounding the application of the Musyarakah Mutanaqisah (MMQ) contract in Islamic housing finance in Indonesia. MMQ, as a sophisticated Islamic jurisprudential (fiqh) innovation, is designed to offer an equitable alternative to debt-based financing models. However, this study identifies a fundamental tension between the ideals of fiqh and the realities of its implementation in the Indonesian financial market. The main findings indicate that although MMQ is theoretically a genuine partnership product that accommodates scholarly differences of opinion (ikhtilaf), its practical application often faces significant challenges. These challenges include a substantial gap in risk-sharing mechanisms, where risks tend to be disproportionately transferred to the customer; a fundamental conflict with the national legal framework concerning collateral (the Mortgage Law or Undang-Undang Hak Tanggungan), which is based on a debtor-creditor relationship; and a critical evaluation of its fulfillment of the higher objectives of Islamic law (Maqasid al-Shariah). This paper concludes that despite MMQ's strong jurisprudential and regulatory legitimacy from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and the Financial Services Authority (OJK), there is a "substantive gap" that needs to be addressed for this product to realize the essence of justice and partnership that forms its philosophical foundation.